Aceh sebagai Pusat Peradaban Islam: Rekonstruksi Sejarah dan Ekspresi Budaya - Zahrul Akbar (Al-Widad, 2024)
Basically, studies on Aceh as a center of Islamic civilization are ideally conducted in an integrative manner by linking historical dimensions, social systems, and cultural expressions. However, in reality, most existing research remains partial and fragmented. This study aims to reconstruct the role of Aceh as a center of Islamic civilization in the Malay–Indonesian world and to analyze the relevance of this legacy in the contemporary context. The method employed is library research using a qualitative descriptive–analytical approach through historical–cultural analysis of primary and secondary sources validated by data triangulation. The findings indicate that Aceh’s Islamic civilization was formed through a process of peaceful Islamization, the strengthening of sultanate institutions, networks of scholars, the dayah education system, the integration of Islamic law and local customs, and sustained religious cultural expressions. This legacy remains relevant in the face of modernization as it functions as a framework of public ethics, social capital, and a foundation for the formation of collective identity. This study contributes to the development of Islamic civilization studies in the Nusantara by offering an integrative perspective that connects history, social structure, and culture as a single analytical unity.